Miniaturized Biosensors Based on Lanthanide-Doped Upconversion Polymeric Nanofibers - Neha Dubey; Sudeshna Chandra (Biosensors, 2024)
Electrospun nanofibers possess a large surface area and a three-dimensional porous network that makes them a perfect material for embedding functional nanoparticles for diverse applications. Herein, we report the trends in embedding upconversion nanoparticles (UCNPs) in polymeric nanofibers for making an advanced miniaturized (bio)analytical device. UCNPs have the benefits of several optical properties, like near-infrared excitation, anti-Stokes emission over a wide range from UV to NIR, narrow emission bands, an extended lifespan, and photostability. The luminescence of UCNPs can be regulated using different lanthanide elements and can be used for sensing and tracking physical processes in biological systems. We foresee that a UCNP-based nanofiber sensing platform will open opportunities in developing cost-effective, miniaturized, portable and user-friendly point-of-care sensing device for monitoring (bio)analytical processes. Major challenges in developing microfluidic (bio)analytical systems based on UCNPs@nanofibers have been reviewed and presented.